2021
DOI: 10.1016/j.ajodo.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, limitations, and solutions for orthodontists during the coronavirus pandemic: A review

Abstract: Objectives Orthodontic patients around the world had to miss appointments during the early months of the COVID-19 pandemic. A significant problem with this virus is its high transmission power. Asymptomatic patients can transmit the virus. This aim of this review is to examine orthodontic emergency situations and the necessary strategies and measures for emergency and non-emergency during the coronavirus pandemic. Methods The following databases were comprehensively sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 90 publications
0
16
0
3
Order By: Relevance
“…Quite unexpectedly, in the present study, there was no substantial increase observed in the interest according to the phrase “braces pain” during the first lockdown period that occurred in the spring of 2020. A lot of orthodontics offices were closed due to the COVID-19 disease [ 18 ], which caused the cancellation of orthodontic visits, especially in the early phase of pandemic outbreak [ 6 ] as it was recommended to consider only urgent cases [ 2 ]. The same measure to control the viral spread was undertaken in the year 2003; dental visits were postponed for at least a one-month period for patients with SARS [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite unexpectedly, in the present study, there was no substantial increase observed in the interest according to the phrase “braces pain” during the first lockdown period that occurred in the spring of 2020. A lot of orthodontics offices were closed due to the COVID-19 disease [ 18 ], which caused the cancellation of orthodontic visits, especially in the early phase of pandemic outbreak [ 6 ] as it was recommended to consider only urgent cases [ 2 ]. The same measure to control the viral spread was undertaken in the year 2003; dental visits were postponed for at least a one-month period for patients with SARS [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…If they were to be carried out, dedicated screening of the patients as well as triage, stringent infection control protocols and higher ventilation and disinfection should be introduced in orthodontics offices. The federal, state or local public health guidelines should be followed as well during the pandemic [ 2 , 5 , 6 ]. According to Bilder et al, 85% of orthodontic patients experience an emergency visit during the orthodontic treatment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present clinical cases, the DM system was crucial and essential to achieve an appropriate interceptive therapy in a growing subject, thus avoiding a more complex treatment (in case 1), and to closely monitor (every 7 days) an adult patient who was in a hurry to improve the esthetics of his smile (in case 2). It can be concluded for these particular cases that without the DM system, it would not have been possible to achieve the same results, considering the period of the pandemic lockdown, which increased the use of virtual consultation [ 17 ]. Above all, the orthodontic treatments were monitored with periodic scans at every alignment change.…”
Section: Discussionmentioning
confidence: 99%
“…Tiene como desventaja el nivel de toxicidad, que puede causar irritación, ulceración y quemaduras de la piel y las mucosas; también puede causar irritación a los ojos y al sistema respiratorio. Aparte de los problemas de toxicidad, la solución a base de aldehídos causa corrosión y oxidación de los instrumentos de acero inoxidable que comprenden la mayoría de los instrumentos dentales y de ortodoncia (Cabrera-Tasayco et al;Carvalho et al;Khatri et al;Ministerio de Salud, 2018;Turkistani;Marín;Malekshoar et al, 2021).…”
Section: Discussionunclassified